2010
DOI: 10.1111/j.1365-2591.2010.01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Root canal debridement using manual dynamic agitation or the EndoVac for final irrigation in a closed system and an open system

Abstract: The null hypothesis was rejected; the presence of a sealed apical foramen adversely affected debridement efficacy when using manual dynamic agitation but not the EndoVac. Apical negative pressure irrigation is an effective method to overcome the fluid dynamics challenges inherent in closed canal systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 39 publications
7
92
0
6
Order By: Relevance
“…28 Meanwhile, during MDA, it is possible that the air bubble in the apical region is eliminated during manual K-file insertion, but the air entrapment reoccurs during removal of the K-file; hence, MDA can result in more debris in the apical regions of the root canal. 29 Our results are in agreement with the previous study by de Gregorio et al, 19 using ultrasonic and sonic (EndoActivator) activations in lateral canals, wherein they found irrigation in the apical third (at 4.5 and 2 mm from working length) better than that with traditional needle irrigation alone. The results of our study are in contrast to a previous study by Klyn et al, 26 wherein they found no statistically significant difference for canal cleanliness between ultrasonic and sonic groups.…”
Section: Discussionsupporting
confidence: 83%
“…28 Meanwhile, during MDA, it is possible that the air bubble in the apical region is eliminated during manual K-file insertion, but the air entrapment reoccurs during removal of the K-file; hence, MDA can result in more debris in the apical regions of the root canal. 29 Our results are in agreement with the previous study by de Gregorio et al, 19 using ultrasonic and sonic (EndoActivator) activations in lateral canals, wherein they found irrigation in the apical third (at 4.5 and 2 mm from working length) better than that with traditional needle irrigation alone. The results of our study are in contrast to a previous study by Klyn et al, 26 wherein they found no statistically significant difference for canal cleanliness between ultrasonic and sonic groups.…”
Section: Discussionsupporting
confidence: 83%
“…Because of the inability to analyse commonly used irrigant penetration and distribution in the root canal system, researchers have recently relied on the radiographic tracing of radiopaque solutions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), or in the observation of cleared teeth (1-3), using sodium hypochlorite (NaOCl) solutions made directly visible by the addition of dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of shaping is to achieve an appropriate surgical canal while cleaning is simultaneously achieved by removing both living and decaying organic matter along with any material contained within the canals, thereby eliminating microbial contamination and creating favorable conditions for healing [4].…”
Section: Introductionmentioning
confidence: 99%